Leadership : the current state of play - Howieson, W. B. (Emerald Publishing Limited, 2018)
Leadership: The Current State of Play seeks to combine current academic and practitioner thinking to present an illuminating and accessible overview of historical and contemporary leadership thought.
Includes index.
Keywords: Leadership.; Business & Economics -- Leadership.; Management: leadership & motivation.; elektronické knihy; electronic books